2005
DOI: 10.1007/s00432-005-0066-4
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-type plasminogen activator activity in morphologically normal tissues adjacent to gastrointestinal carcinomas is associated with the degree of tumor progression

Abstract: "Morphologically normal tissues" adjacent to carcinomas present abnormal t-PA activity that is associated with the degree of tumor progression. Assaying of this activity could be useful as a predictive parameter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…However, Vidal et al showed that the preoperative serum uPA levels in gastric cancer patients were similar to those in the control subjects . High expression of uPAR, uPA, and PAI‐1 was observed in gastric tumors compared to normal tissues . Further, the expression of uPA and uPAR in gastric cancer was correlated to poor outcome .…”
Section: Clinical Relevance Of Components Of Upa System In Human Cancersmentioning
confidence: 99%
“…However, Vidal et al showed that the preoperative serum uPA levels in gastric cancer patients were similar to those in the control subjects . High expression of uPAR, uPA, and PAI‐1 was observed in gastric tumors compared to normal tissues . Further, the expression of uPA and uPAR in gastric cancer was correlated to poor outcome .…”
Section: Clinical Relevance Of Components Of Upa System In Human Cancersmentioning
confidence: 99%
“…Tissue plasminogen activator (tPA) is the intra-vascular counterpart to uPA, involved in fibrin degradation to prevent blood clot formation [13]. However, tPA does not appear to play a significant role in the development of solid tumours [16].…”
Section: Introductionmentioning
confidence: 99%